Effects of In-Office and Home Bleaching Gels on the Surface Mercury Levels of Dental Amalgam - Oskoee, Parnian Alizadeh; Kahnamoui, Mahdi Abed; Oskoee, Siavash Savadi; Zadfattah, Firooz; Pournaghi-Azar, Fatemeh (European Journal of Dentistry, 2010)
Objectives: The aim of this study was to evaluate the effect of different in-office and home bleaching gels on the surface mercury levels of dental amalgam.Methods: Sixty disk-shaped amalgam specimens (GS-80, SDI- Australia) were prepared and randomly divided into the following treatment groups: 1. Distilled water (control); 2. 15% home-bleach carbamide peroxide (Opalescence PF, Ultra dent, USA) applied for 6 h/day for 3 weeks; and 3. 35% in-office bleach carbamide peroxide (Opalescence Quick, Ultradent) applied for 30 min/week for 3 weeks. Levels of mercury were measured as weight percentages using an energy dispersive x-ray micro-analyzer detector connected to an electron microscope. Data was analyzed using one-way ANOVA and a post hoc Tukey tests (P<.05).Results: There were no significant differences between the surface mercury levels measured following treatment with the tested home-bleach and in-office bleach products (P=0.71). However, both materials yielded significantly more mercury levels than that of the control group (P<.001).Conclusions: The tested bleaching products significantly elevated the surface mercury levels of amalgam in vitro. (Eur J Dent 2010;4:23-27)
Keywords: Tooth bleaching; Dental amalgam; Carbamide peroxide; Mercury